Effect of Nutrients on Bulking Behavior of Potato at Different Growth Stages - Adhikari, R.C.; Shrestha, M.D. (Journal of the Institute of Agriculture and Animal Science, 2002)
An experiment was conducted at Rampur, Chitwan, Nepal in 2000 to assess the bulking behavior of two potato cultivars (Kufri Sindhuri and Desiree) at different nutrient levels (0:0:0, 50:50:50, 100:50:50, 100:75:50, 100:75:100, 100:100:100 and 150:100:100 N, P2O5 and K2O kg ha-1) under humid sub-tropical in sandy loam soils. Plant height, number of stems and tubers, fresh weight of leaf, stem, tuber and dry weight of tubers, yield at maturity and N, P2O5, K2O uptake by tubers were recorded at 15 days interval during the crop growth period. Maximum bulking rate of tuber was 16.81 g and 9.35 g hill-1 day-1 in Kufri Sindhuri and Desiree, respectively. Kufri Sindhuri produced significantly more tuber numbers compared to Desiree at all the growth stages. However, application of nutrients did not show significant difference in tuber number in both the cultivars. In Kufri Sindhuri maximum tuber bulking rate was 18.75 g hill-1 day-1 in the combinations of 100:75:100 NPK kg ha-1, whereas in Desiree it was 10.5 g hill-1 day-1 in the treatment 100:50:50 NPK kg ha-1 during 45-60 days after planting (DAP). Total tuber weight significantly correlated with leaf and stem weight, N, P2O5 and K2O uptake in both the cultivars Keywords: Potato, bulking rate, nutrients, tuber yield, nutrient uptake J. Inst. Agric. Anim. Sci. 23:15-20.